People With High Autistic Traits Show Fewer Consensual Crossmodal Correspondences Between Visual Features and Tastes - Chen, Na; Watanabe, Katsumi; Wada, Makoto (Frontiers in Psychology, 2021)
Crossmodal correspondences between visual features (e.g., color/shape) and tastes have been extensively documented in recent years. Visual colors and shapes have been shown to consensually matched to specific tastes. Meanwhile, individuals with autism spectrum disorder are reported to have atypical sensory processing and deficits in multisensory integration. However, the influence of autistic traits on the formation of such correspondences is relatively unknown. Here, we examined whether autistic traits could influence visual–taste associations using an online questionnaire survey among Japanese participants. The results showed that the participants exhibited strong color–taste, shape–taste, and shape–color associations, and the proportions of choosing the consensual color–taste/shape–color associations were significantly associated with autistic traits. The participants with higher autistic quotient scores chose fewer of the consensual color–taste/shape–color associations, while there was no difference in choosing shape–taste associations. We interpreted the results as statistical learning with a reduced prior knowledge effect in participants with higher autistic quotient scores.